One stent versus two stents for distal LM PCI: insights from the experience of a high volume center. (25th November 2020) - Santos, R; Nobre-Menezes, M; Carrilho-Ferreira, P; Jorge, C; Francisco, A.R; Infante-Oliveira, E; Duarte, J; Cardoso, P; Torres, D; Aguiar-Ricardo, I; Rigueira, J; Rodrigues, T; et al.
Abstract: Introduction: Distal left main (LM) PCIremains a challenge. One of the most debated issues is whether to use a single vs 2 stent provisional strategy. While most studies and guidelines favour a single stent strategy, the recent DK-CRUSH V trial has shown better results with a 2 stent strategy. Objective: To evaluate the performance of a single vs dual stent strategy for LM PCI in a real-world population setting. Methods: Single-center procedural prospective registry of patients (pts) submitted to LM PCI from 2015–2018, with retrospective event analysis. Demographic, clinical data and procedure characteristics were analysed. Results were obtained with χ 2 test, T student test, Kaplan-Meier survival analysis, logistic and Cox regression. Results: 100 pts (73 men; 69±11 years) were included. Co-morbidities were very frequent (85 had hypertension, 54 had diabetes, 71 had dyslipidemia and 39 were past smokers). 32 had reduced LVEF (<40%) and 45 previous CABG. The decision to proceed to PCI vs surgery was undertaken individually by the local HeartTeam. Most of the procedures (57) were in an acute coronary syndrome setting (11 in STEMI, 7 with cardiogenic shock). The anatomical distribution of the lesions was: distal in 69 pts (61 involved the LAD and or Cx ostium), mid shaft in 7 pts, ostial in 18 pts and diffuse in 6 pts. Protected left main PCI encompassed 41% of the procedures. The complication rate was 7%. During a mean follow-up of 866±400 days, there were 4 peri-procedural deaths, 1-year mortality rate of 10% and 22 pts died overall. In pts submitted to distal LM PCI, a single stent was used in 49 pts (66%) versus a 2 stent approach in 23 pts (31%). The only significant difference between these groups were diabetes (66% in the single stent vs 32% in the 2 stent group, p=0.006) and protected LM (51% in the single stent vs 26.1% in the two stent group, p=0.046). While a 2 stent strategy was associated with higher mortality by Kaplan Meyer analysis (LogRank = 11.07, p=0.001), it was not an independent predictor of mortality in Cox regression. Cox univariate analysis identified LVEF <40% (OR 2.2, CI 1.01–4.9, p=0.047) and complications (OR 3.1, CI 1.4 – 6.9, p=0.004) as the only predictors of death. In multivariate analysis, only the latter was an independent predictor of mortality (OR 2.6, IC 1.1–5.9, p=0.028). The use of a 2 stent strategy was significantly associated with complications (χ 2 =5.1 p=0.024)) and was the only independent predictor of it (OR 3.8, IC 1.1–12.8, p=0.03). This was true even in the subgroup of protected LM PCI. Conclusion: In a real-world setting of challenging LM PCI cases, a single stent strategy for distal LM PCI performed better. The use of 2 stents was an independent predictor of complications, strongly associated with increased risk of death. While a LM PCI must be undertaken on an individual basis, a single stent provisional strategy, whenever feasible, seems to be the best option. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Hospita Santa Maria